Bioaerosol Sampling at a Live Animal Market in Kunshan, China: A Noninvasive Approach for Detecting Emergent Viruses. (22nd April 2020) - Wang, Xinye; Bailey, Emily S; Qi, Xian; Yu, Huiyan; Bao, Changjun; Gray, Gregory C
Abstract : From October to December 2018, periodic bioaerosol sampling was conducted at a live bird market in Kunshan, China. Sixty-six (55%) of 120 samples had molecular evidence of avian influenza viruses. Four yielded live H9N2 virus after egg culture.